HPTLC Method for Simultaneous Estimation of Nimesulide and Diclofenac Sodium in Capsule - G. Walode, Sanjay; N. Maliye, Amit; R. Gupta, Krishna; V. Kasture, Avinash; G. Wadodkar, Sudhir; R. Tajne, Madhukar (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive high performance thin layer chromatographic (HPTLC) method has been developed and validated for simultaneous estimation of nimesulide and diclofenac sodium in capsule. It was performed on TLC plate precoated with silica gel 60 GF254 as a stationary phase using mobile phase comprising of n-hexane : ethylacetate : chloroform : glacial acetic acid ( 8:1:1.5:0.5) and the detection was carried out in absorbance/reflectance mode at 256 nm showing Rf value 0.3 for nimesulide and 0.57 for diclofenac sodium. The per cent estimations of labelled claims of nimesulide and diclofenac sodium from marketed tablet were found to be 99.92 ± 0.2779, 100.65 ± 0.9630 by height and 99.93 ± 0.4562, 99.27 ± 0.5974 by area respectively. The method was validated in terms of accuracy, precision, specificity and ruggedness. Linearity was observed between 1.0–3.2 μg for nimesulide and 0.5–1.6 μg for diclofenac sodium. The recoveries of drugs by standard addition method were found in the range 99.14 and 100.99 for both the drugs. The proposed method is precise and accurate and can be used for routine analysis of nimesulide and diclofenac sodium in capsule formulation.